Cylindrical shells made of stainless steel - investigation of postbuckling = Powłoki cylindryczne ze stali nierdzewnej - badanie stanów pokrytycznych - Stehr, Sebastian; Stranghöner, Natalie (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The relevant load case of open thin-walled shells is often wind loading during construction. Because of the missing stabilization effect of the roof they show a very high sensitivity to buckling which results into higher wall thicknesses.
Keywords: cylindrical shells; stainless steel; wind loading; postbuckling; EN 1993-1-6; powłoka cylindryczna; stal nierdzewna; obciążenie wiatrem; stan pokrytyczny